Kidney Injury Molecule-1 as a Promising Biomarker for Acute Kidney Injury in Premature Babies - Genc, Gurkan; Ozkaya, Ozan; Avci, Bahattin; Aygun, Canan; Kucukoduk, Sukru (American Journal of Perinatology, 2013)
Objective To evaluate the role of urinary kidney injury molecule-1 (uKIM-1) in early determination of renal injury in premature infants with respiratory distress syndrome (RDS).Study Design Forty-eight premature babies hospitalized in the neonatal intensive care unit were included in the study and divided into three groups: group I, healthy premature infants; group II, preterm infants with RDS without acute kidney injury (AKI); group III, preterm infants with RDS and AKI. uKIM-1 and creatinine along with serum creatinine levels were measured with enzyme-linked immunosorbent assay on days 1, 3, and 7 of life.Results On day 1, uKIM-1 levels in babies with RDS and AKI were higher than the other two groups. In this group, a significant increase in uKIM-1 levels were detected on day 3 (p = 0.015). The sensitivity and specificity of uKIM-1 were calculated as 73.3% and 76.9%, respectively, along with the increase of 0.5 ng per milligram of creatinine of uKIM-1 in day 3, when compared with values on day 1. Elevated uKIM-1 on day 7 was found to increase the risk of death by 7.3 times.Conclusion Serial uKIM-1 measurements can be used as a noninvasive indicator of kidney injury and uKIM-1 can be an ideal biomarker in premature infants.
Keywords: acute kidney injury; premature; respiratory distress syndrome; KIM-1